Ultrafast Terahertz Superconductor Van der Waals Metamaterial Photonic Switch - Kaveh Delfanazari (Advanced Photonics Research, 2024)
The high‐temperature layered superconductor (HTS) BSCCO is one of the key quantum material platforms in THz science and technology. Compact, stable, and reliable BSCCO THz photonic integrated circuit components can be developed to effectively and efficiently control and manipulate THz wave radiation, especially for future communication systems and network applications. Herein, the design, simulation, and modeling of ultrafast THz metamaterial photonic integrated circuits are reported on a few nanometer‐thick HTS BSCCO van der Waals (vdWs), capable of the active modulation of phase with constant transmission coefficient over a narrow‐frequency range. Meanwhile, the metamaterial circuit works as an amplitude modulator without significantly changing the phase in a different frequency band. Under the application of ultrashort optical pulses, the transient modulation dynamics of the THz metamaterial offer a fast‐switching timescale of 50 ps. The dynamics of picosecond light–matter interaction, Cooper pairs breaking, photoinduced quasiparticles generation and recombination, phonon bottleneck effect, and emission and relaxation of bosons in BSCCO vdW metamaterial arrays are discussed for the potential application of multifunctional superconducting photonic integrated circuits in communication and quantum technologies.